The Hebrew of the Dead Sea scrolls and Ben Sira : proceedings of a symposium held at Leiden University, 11-14 December 1995 - Muraoka, T.; Elwolde, J. F. (Studies on the Texts of the Desert of Judah, 1997)
In December 1995 an international symposium was held in Leiden, concerning the subject of the Hebrew of the Dead Sea Scrolls and the book of Ben Sira. The papers, presented at this symposium, are collected in this volume. The papers deal with various aspects of grammar, syntax, and lexicon of Hebrew texts of the Judean Desert. They include the first publications of a Nahal Hever text, and the important apocryphal book of Ben Sira.